Rethinking Public Relations in Crisis Management and Employee Engagement in the Nigerian Shippers’ Council - Abigail Olubukola Irele; Bashir Ambi-Mohammed (PT Agung Media Publisher, 2025)
Organisations and businesses face complex challenges in their daily operations, both intrapersonal and interpersonal, which can impact their effectiveness, reputation, and employee job satisfaction. Ineffective crisis management may lead to low morale, decreased productivity, and increased turnover rates. This study examines the relationship between public relations tools, crisis management, and employee job satisfaction in the Nigerian Shippers' Council. This study is based on Stakeholder Theory and employs a correlational survey research design. A purposive sampling technique was used, with total enumeration yielding 433 respondents. Data were collected through structured questionnaires and analyzed using descriptive and inferential statistics. Findings indicate that 98.3% of respondents preferred WhatsApp group communication due to its interactive and inclusive nature. Furthermore, press releases and media briefings were minimally used during crises, with 80% and 76.8% of respondents, respectively, stating they were only occasionally employed. The study highlights the importance of digital communication platforms, particularly WhatsApp groups and online surveys, in enhancing real-time engagement with employees and stakeholders. It is recommended that the Nigerian Shippers’ Council prioritize these tools to improve crisis management strategies and boost employee job satisfaction.